A Knowledge Enhancement about Business Potential for Smart Residence Technology System in Thailand for Communities - Jivacate, Achara; Rakwichian, Wattanapong; Thanarak, Prapita; Wongpanyo, Watchara; Vichanpol, Bunyawat; Chailuecha, Chatkaew; Werasukho, Pirachaya (ASEAN Journal of Education, 2018)
Smart residence is one of advanced technologies, which has been gradually and increasingly recognized nowadays. Smart residence is based on home automation providing the selling points of convenience and image of the resident. The concept of home automation was used in Thailand over the past 20 years. However, nowadays it is likely developed into smart residence. Since Thailand has more global warming awareness caused by increasing amounts of fossil fuel. Smart residence is considered as one alternative to reduce electrical energy generated from fossil fuel. The initial stage to develop smart residence, the first principle approach is that the resident uses electricity produced by electricity providers and self-supply energy supplied with renewable energy. Also, energy storage system and information and communication technologies must be installed. Consequently, smart residence system will be developed to be very desirable residence, home-area network and sustainable smart town. In the future, the complete system will comprise: monitor; forecast; manage and control. The purpose of this study is to enhance understanding and to address Thailand’s readiness to move forwa business for smart residence technology system in various aspects. The aspect of policy is to boost renewables, smart grid system, energy storage system, intelligent charging system (V2G). Furthermore, the customers (users), economy and business are highlighted to support business for this smart residence technology system. The up-to-date information of this paper is obtained from literature reviews, purposive in-depth interviews and questionnaires with qualitative SWOT analysis method. Some results show Thailand energy policy availability, considerable purchasing power and payment for benefit and satisfaction achievement of Thais. The implications of these findings clearly reflect business potential for smart residence technology system in Thailand.